PENGARUH KOMPONEN ARUS KAS TERHADAP HARGA SAHAM PADA PERUSAHAAN BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dewi Saptantinah Puji Astuti, Tomi Dwi Permadi, Bambang Widarno & (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2017)
Investors in making investments need to pay attention to information operatingcash flow, cash flow investing and financing cash flows, due to the cash flowstatement is relatively easier to interpret and relatively difficult to manipulate. Thepurpose of this study was to analyze the significance of the effect of operating cashflow, cash flow investing and financing cash flows partially or simultaneously to thestock price at the state-owned enterprises listed on the Indonesia Stock Exchange.This study uses a case study at state-owned enterprises listed on the Indonesia StockExchange, the type of data used quantitative and qualitative data, the data sourceused secondary data. The population in this study are all state-owned enterpriseslisted on the Indonesia Stock Exchange totaling 20 companies. The samples usedwere 19 companies, with a sampling technique used purposive sampling. Dataanalysis techniques used classical assumption test and multiple linear regressionanalysis. In conclusion that: Operating cash flow and investing cash flows positiveeffect is not significant to the stock price at the state-owned enterprises listed on theIndonesia Stock Exchange, while financing cash flows significant positive effect onstock prices at state-owned enterprises listed on the Indonesia Stock Exchange.Simultaneously, operating cash flow, cash flow investing and financing cash flowssignificantly influence stock prices at state-owned enterprises listed on the IndonesiaStock Exchange. Researchers further in conducting research on the factors thataffect stock prices can add other independent variables, such as earnings growth,financial ratios, and so forth.Keywords: operating cash flow, investing cash flows, financing cash flows, stockprices